Treatment options for refractory and difficult to treat seizures: focus on vigabatrin - Tolman JA; Faulkner MA (Dove Medical Press, 2011)
Justin A Tolman, Michele A FaulknerSchool of Pharmacy and Health Professions, Creighton University, Omaha, Nebraska, NE, USAAbstract: Complex partial seizures are often refractory to current pharmacological therapies. These difficult to treat seizures are typically managed using multiple antiepileptic drugs (AEDs). AEDs as a group are frequently associated with significant adverse drug effects, multiple drug interactions, and numerous potential clinical complications due to their individual pharmacokinetic profiles and unique drug properties. Recently, the approval of vigabatrin by the US Food and Drug Administration has necessitated that clinicians re-evaluate these risk-benefit relationships and determine where the drug fits within the treatment scheme for the management of complex partial seizures. This review will facilitate that re-evaluation through a brief review of AEDs used in the treatment of complex partial seizures, followed by a focused discussion on vigabatrin.Keywords: vigabatrin, complex partial seizures, refractory seizures, risk evaluation and mitigation strategy, epilepsy